Characterization of the complete chloroplast genome of Dendrobium findlayanum Par. et Rchb. f. 1874 (Orchidaceae). Issue 4 (3rd April 2022) - Chen, Cui-Ying; Tan, Hui; Chen, Rui; Zhang, Feng-Ping
Abstract: Dendrobium findlayanum Par. et Rchb. f. 1874 has the high ornamental and medicinal value. Here, we report the first complete chloroplast genome of D . findlayanum . The complete chloroplast genome of D . findlayanum is 153, 713 bp in length with 120 genes, including 75 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The total content of GC of the whole genome is 37.46%. Phylogenetic analysis indicated that D . findlayanum was closely related to other species in Dendrobium, and this study provides new genetic resources for species identification and phylogenetic analyses in Dendrobium .